2012
DOI: 10.1016/j.cnur.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Participatory Research and Smoking Cessation Interventions: A Review of the Evidence

Abstract: SYNOPSIS This article presents a review of the evidence on the use of community-based participatory research (CBPR) and smoking cessation interventions. An overview of CBPR is provided, along with a description of the search methods and quality scoring. Research questions are explored to determine: if CBPR improves the quality of research methods and community involvement in cessation intervention studies; and, cessation outcomes when using CBPR approaches. Results of the review are provided along with a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…The current study, however, demonstrated a higher retention rate compared to previous studies, with 91% of participants retained at 12 months in the current study, compared to 70%–75% six-month retention rate in the other similar studies (Okuyemi et al, 2007; Ahluwalia et al, 2006; Cox et al, 2012). These findings support previously reported evidence that a CBPR approach aids in the recruitment and retention of racial and ethnic minority populations (De Las Nueces et al, 2012; Andrews et al, 2012b). …”
Section: Discussionsupporting
confidence: 92%
“…The current study, however, demonstrated a higher retention rate compared to previous studies, with 91% of participants retained at 12 months in the current study, compared to 70%–75% six-month retention rate in the other similar studies (Okuyemi et al, 2007; Ahluwalia et al, 2006; Cox et al, 2012). These findings support previously reported evidence that a CBPR approach aids in the recruitment and retention of racial and ethnic minority populations (De Las Nueces et al, 2012; Andrews et al, 2012b). …”
Section: Discussionsupporting
confidence: 92%
“…Although the majority of published CBPR studies have been conducted with racial/ethnic minority and low-SES populations, emerging literature indicates CBPR methods can be similarly effective in recruiting participants from other underrepresented/marginalized groups such as sexual minority populations (Bryant et al, 2014; Rhodes et al, 2014), persons with disabilities (Nicolaidis et al, 2013), immigrants and refugees (Njeru et al, 2015), and individuals experiencing homelessness and co-occurring mental illness (Henwood et al, 2013). In a notable example underscoring the potential role of CBPR to foster inclusion, an evidential review of CBPR and smoking cessation interventions in marginalized communities found that studies with relatively low community involvement generally had challenges with participant recruitment (Andrews et al, 2012). …”
Section: The Connect Frameworkmentioning
confidence: 99%
“…13 Their work highlights the value of engaging community stakeholders in planning, implementing and evaluating smoking cessation interventions. In their qualitative study, Wallen et al solicited suggestions from smokers for designing cessation interventions that focused largely on the principles of community-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…These included: defining the community; involving partners in every step of the research; adhering to the ideal CBPR model; investing the time necessary for developing trust and nurturing partnerships; and navigating the complex IRB requirements for community interventions. 13 Fortunately, CEASE benefited from the long-term community-campus partnership that started in 2002 and has been overseen by a strong Community Action Board comprised of community residents, leaders, and representatives of schools and faith-based organizations. The application for funding this study was jointly prepared by the partnership.…”
Section: Discussionmentioning
confidence: 99%